Inovasi produk olahan Singkong menjadi Singkong Frozen untuk meningkatkan pendapatan masyarakat - Halida Sophia; Andi Dahliaty; Titania Tjandrawati Nugroho; Sri Helianty (Unri Conference Series: Community Engagement, 2020)
The cassava's production arm was quite abundant. Human ratings generally revolved around plantations and in rungs industries, much of which was said in cassava commodities. Most people consume cassava in the simple way of being boiled, fried, made in chips, and so on. In order not to dull the flavor of traditional foods but to be increasingly ogled by the styrofoampurvets, it is possible to make the products of the Singkong processed innovation into cassava frozen. The public's devoted activity is to helping people improve the economy, providing added insight and skill to processing cassava through cassava frozen and helping people form a group of tapioca women (KWT). The method used in this dedicated activity is by counseling between socializing and training and by demonstrations of Singkong frozen production. This activity involves women of family welfare development and housewives in three neighborhood associations is number 01, 02, and 03 at citizens association 12, Mentangor village districts,Tenayan Raya city districts. The result of this activity is that the target public seems enthusiastic about the material presented and has increased participants' knowledge and insight on assava frocenas are 100%.